Pengembangan Lembar Kerja Siswa Berbasis Discovery Learning - Lucy Asri Purwasi; Nur Fitriyana (Jurnal Pendidikan Matematika:Judika Education, 2020)
The purpose of this study is to produce discovery learning based on valid, practical and effective discovery. This research is a research development using a modification of the development model of 4-D (Four D-Models) learning tools, consisting of defining, designing, developing, and disseminating. The instruments of this study were the worksheet validation sheets, practical sheets, student worksheets and worksheet effectiveness sheets. Some stages in this research consist of the development study phase and the evaluation phase to test the effectiveness and test the feasibility of new student worksheets for use in learning. Validity category research results obtained an average of 3.7 with a valid category. In the practicality category the worksheets were developed based on student assessments with an average of 3.83 and based on teacher ratings of 3.63 by being in the practical category. The results of the effectiveness of learning obtained by the achievement of teacher activity with an average of 4.37 with active categories. For observations of student activities during learning takes place an average of 3.73 with the category is in active criteria. In conclusion, the development of Discovery Learning based on LKS is categorized as valid, practical and effective to be used by students in building material on flat sides, cubes and beams. Keywords: Development, Worksheet, and Discovery Learning.